EXPLORING THE IMPACT OF MIND MAPPING AND CLUSTERING TECHNIQUES ON RECOUNT TEXT LEARNING FOR 10TH GRADE STUDENTS AT SMK NEGERI 1 DHARMA CARAKA - Harefa, Febriwan; Tampubolon, Sahlan; Pasaribu, Arsen Nahum (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
This research aimed to determine the effectiveness of clustering and mind mapping techniques in enhancing the writing abilities of 10th-grade students at SMK Negeri 1 Dharma Caraka, Gunungsitoli Selatan, specifically in Recount text learning. The quasi-experimental study involved 231 students across seven classes, with a sample of 93 students divided into three groups: 31 students using the mind mapping technique, 31 using the clustering technique, and 31 using conventional methods. Data were analyzed using SPSS 29.00. The findings revealed significant improvements in the students' writing abilities with both techniques. The mind mapping group's post-test mean score was 84.51, up from a pre-test mean of 51.451. The clustering group's post-test mean was 89.482, compared to a pre-test mean of 54.838. An ANOVA analysis showed average scores of 84.51 for the mind mapping technique, 89.48 for the clustering technique, and 78.09 for the conventional technique. Overall, the clustering technique proved to be more effective than the mind mapping technique in improving the students' writing skills in Recount text learning. Thus, clustering is recommended for enhancing writing abilities in this context.